Upaya Hukum Dalam Penyelesaian Sengketa Pajak Pada Pengadilan Pajak: Suatu Perspektif Keadilan - Aulia, Ismiani; Marinda Machdar, Nera (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This research aims to examine the mechanism of tax dispute resolution in Indonesia, with a focus on the differences in characteristics between tax dispute resolution and the general judicial system. The research method used is normative legal research, utilizing a legislative approach (positive law). The research findings conclude that tax disputes in Indonesia, especially those related to Tax Assessment Letters, can be resolved through administrative means, such as filing objections, as well as through tax courts, which involve legal remedies like appeals and lawsuits. Additionally, the research also discusses the role and position of the Tax Court in Indonesia, along with the obstacles that hinder the tax dispute resolution process in this institution, such as the limited availability of court locations and significant penalties. This study is expected to enhance understanding of tax judiciary and advocate for the establishment of a Tax Court that is more professional, independent, and trustworthy.